Frege: Aufsätze zur Logik und Sprachphilosophie - Demmerling, Christoph; Kienzler, Wolfgang; Rohr, Tabea (Klassiker auslegen, 2023)
Frege's essays "Function and Concept," "On Sense and Meaning," and "Concept and Object" form a unity in terms of both their origins and their reception history, and have long established themselves as two of the key texts of analytical philosophy. This volume presents and provides commentary on them together. Also conceived of as a course book, this volume provides access to Frege as an eminent, lively classic author